Analisis Perlakuan Akuntansi Terhadap Aktiva Tetap Pada PT. Agung Podomoro Land Tbk - Yulianti, Wiwit Rohaeni; Romadhona, Puspita (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Along with the times, the need for information and the quality of financial reports is increasing. Financial statements provide an overview of the company's financial condition that is important for shareholders and other stakeholders. The company aims to improve shareholder welfare through optimal profit generation. One important component in the financial statements is fixed assets, which has a big role in business operations, especially in the property sector such as PT Agung Podomoro Land Tbk. This study aims to analyze the accounting treatment of fixed assets at PT Agung Podomoro Land Tbk. The method used is descriptive analysis of secondary data from the company's financial statements. The results showed that PT Agung Podomoro Land Tbk applies the straight-line method for depreciation of fixed assets with the appropriate useful life. The company also follows PSAK No. 16 on the termination and disposal of fixed assets. Information regarding the value of fixed assets presented in the financial statements has been clearly disclosed, including additions, subtractions, and reclassifications of assets. The implication of this study shows the importance of proper fixed asset management to ensure the accuracy of financial statements and effective decision making.